The Role of Coffee Processing Business Management in Enhancing the Value of Local Coffee Products in Tapin Regency - Zamhuri Rachman; Hamdi Hamdi; Husinsyah Husinsyah; Tumrat Tumrat; Annisa Fitriani (Sean Institute, 2026)
Coffee is one of the strategic plantation commodities that plays an important role in supporting rural economic development, particularly through farmer group–based enterprises and local agro-processing units. Indonesia, as one of the world’s major coffee-producing countries, has diverse coffee types, including Arabica, Robusta, and Liberica. Liberica coffee possesses unique characteristics, distinctive aroma, and strong adaptability to specific land conditions, making it a potential locally based flagship commodity. Coffee quality is not only influenced by cultivation practices but is also strongly determined by post-harvest processing methods that affect physical quality, aroma, and flavor. One widely applied post-harvest method among local coffee enterprises is the natural process (dry process), which involves drying whole coffee cherries without prior depulping and is known to enhance sweetness, fruity aroma, and body. This study was conducted at the Berkah Kopi Tapin farmer group, a local coffee processing unit located in Asam Randah Village, Hatungun District, Tapin Regency, South Kalimantan, which develops Liberica coffee as its main commodity alongside Robusta and Arabica. The research aims to analyze the role of coffee processing business management in supporting value addition of local coffee products, with particular emphasis on Liberica coffee development. A descriptive analytical approach was employed to examine production management, post-harvest processing, and marketing practices. The results are expected to provide empirical insights into management practices implemented by local farmer groups and their potential contribution to enhancing competitiveness and sustainability of local coffee agribusiness in Tapin Regency.